Employment of Literay Tradition In the Polemic Poems of Jarir , Al-Farazdaq and Al-Akhtal (Journal of the College of Education for Women, 2019)
The present study is an academic attempt to show how the threeUmayyad poets ; Jarir ,Al-Farazdaq and Al-Akhtal have skillfully employed old conventions and traditions in theirpoetry to serve a dual purpose of making their ideas striking , memorable and compelling andof reaching eminence as poets.The primary aim of the poets has been to amuse , convince and influence the readers orlisteners of their poetry . as it were, a mirror image of the social , religious and historicalbeliefs , values and customs which prevailed throughout the ages before the emergence.